Impact of heat source/sink towards MHD stagnation flow and heat transfer of GO-TiO2-Ag/Water nanofluid over a shrinking surface - Mohd Nasir, Nor Ain Azeany; Zainuddin, Nooraini; Md Arifin, Norihan; Wahid, Nur Syahirah; Pop, Ioan (Semarak Ilmu Publishing, 2025)
This investigation aims to solve the mathematical modelling of magnetohydrodynamic (MHD) stagnation flow and heat transfer of GO-TiO2-Ag/water nanofluid towards a shrinking surface problem. The model contains the impacts of suction/injection, radiation, magnetic field intensity and heat source/sink parameters. By converting the governing equations into ordinary differential equations with applying similarity conversion and employing the bvp4c built-in solver in MATLAB software, numerical results are attained. Furthermore, the existence of GO as the ternary particles improves more the temperature profile but declining the velocity profile. This investigation promotes substantial understandings into heat transference achievement in MHD stagnation flow towards a shrinking surface, specifically with the interaction of GO particles and heat source/sink influences.